2011
DOI: 10.3109/0886022x.2011.601829
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid and Lovastatin Might Protect Kidney in Renal I/R Injury by Downregulating MCP-1 in Rat

Abstract: Renal ischemia/reperfusion (I/R) injury is a major cause of renal failure. The aim of our study is to explore the role of lysophosphatidic acid (LPA) and lovastatin on renal I/R injury and its mechanism in the rat. Male Wistar rats were randomly divided into sham-operated group; renal I/R for 0 h, 4 h, 12 h, and 24 h groups; LPA treatment group; and lovastatin treatment group (n = 10). Rats were killed to determine the level of monocyte chemotactic protein-1 (MCP-1) in renal tissue, renal function [serum creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Similar findings were observed with plasma IL‐6 levels by Leelahavenichkul et al . in an alternative AKI model and others have reported increased levels of IL‐6 and MCP‐1 in kidney tissues after AKI induced by renal ischaemia and reperfusion (I/R) in rodents with normal kidney function prior to AKI. That model was fundamentally different from the one used in the current study, in which cytokine and chemokine responses within the kidney were equally increased (beside IL‐1β) in rats with CKD regardless of IIR exposure.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were observed with plasma IL‐6 levels by Leelahavenichkul et al . in an alternative AKI model and others have reported increased levels of IL‐6 and MCP‐1 in kidney tissues after AKI induced by renal ischaemia and reperfusion (I/R) in rodents with normal kidney function prior to AKI. That model was fundamentally different from the one used in the current study, in which cytokine and chemokine responses within the kidney were equally increased (beside IL‐1β) in rats with CKD regardless of IIR exposure.…”
Section: Discussionsupporting
confidence: 87%
“…AA-treatment probably lowers the kidney levels of various LPLs that express differently homeostatic actions of the kidney integrity and functions. Gao et al [24] showed that intraperitoneal injection of LPA under ischemia was able to protect against the kidney injury due to ischemia/reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, LPA seems to be protective factor against the renal ischemia-reperfusion injury (I/R) which is important cause of acute renal failure in patients after renal transplantation, major surgical procedures or in hypovolemic shock [19, 20].…”
Section: Introductionmentioning
confidence: 99%